Differential role of M cells in enteroid infection by Mycobacterium avium subsp. paratuberculosis and Salmonella enterica serovar Typhimurium - Alfituri, Omar A.; Blake, Rosemary; Jensen, Kirsty; Mabbott, Neil A.; Hope, Jayne; Stevens, Joanne M. (Frontiers in Cellular and Infection Microbiology, 2024)
Infection of ruminants such as cattle with Mycobacterium avium subsp. paratuberculosis (MAP) causes Johne's disease, a disease characterized by chronic inflammation of the small intestine and diarrhea. Infection with MAP is acquired via the fecal-to-oral route and the pathogen initially invades the epithelial lining of the small intestine. In this study we used an in vitro 3D mouse enteroid model to determine the influence of M cells in infection of the gut epithelia by MAP, in comparison with another bacterial intestinal pathogen of veterinary importance, Salmonella enterica serovar Typhimurium. The differentiation of M cells in the enteroid cultures was induced by stimulation with the cytokine receptor activator of nuclear factor-κB ligand (RANKL), and the effects on MAP and Salmonella uptake and intracellular survival were determined. The presence of M cells in the cultures correlated with increased uptake and intracellular survival of Salmonella, but had no effect on MAP. Interestingly neither pathogen was observed to preferentially accumulate within GP2-positive M cells.